Influence of curcumin natural dye colorant with PMMA-acrylic polyol blended polymer - Abidin, Z.H.Z. (Emerald, 2013)
Purpose - The purpose of this work is to investigate the influence of curcumin dye natural colorant on adhesion, mechanical, thermal and electrochemical properties of blend poly (methyl methacrylate) (PMMA) - acrylic polyol. Design/methodology/approach - Extracted curcumin yellow dye colorant from Curcuma Demostica was mixed with PMMA-acrylic polyol blended polymer in the volume ratios of 9:1, 8:2 and 7:3. The mixtures were applied on pre-treated cold-roll mild steel panels. All of the paint coating samples were subjected to potential time measurement (PTM), rapid impact deformation, differential scanning calorimetry (DSC), cross hatch and Fourier transform infrared spectroscopy (FTIR) tests. Findings - The addition of curcumin dye colorant was able to improve the adhesion, flexibilities and resistance against electrolytes penetration of the blended poly (methyl methacrylate) (PMMA) - acrylic polyol polymer paint system. Cross hatch test studies showed that high amount of curcumin dye colorant (AP30 paint system) had the lowest peel-off coating area from the substrate. The FTIR test had confirmed the high concentration of hydroxyl group in the AP30 sample. The hydroxyl group was able to promote hydrogen bonding between coating substrate interface. The AP30 sample had the highest coating flexibilities when tested with rapid impact test. This was due to the lowest glass transition value T-g which indicated lowest cross linking density in the coating molecules structure. In the PTM test, AP30 paint system had shown the highest rate electrolytes penetration within the AP sample. Research limitations/implications - The composition of curcumin dye colorant in the polymer blend is limited from 10 percent to 30 percent pigment volume concentration. Increasing the amount of lawsone pigment will result inhomogeneous mixtures. Originality/value - The AP paint system is suitable for interior applications. This paint system has to be mixed with suitable additive materials to improve its performance for exterior purpose.